An integrated taxonomic analysis into the identity of Hoplisoma julii (Siluriformes: Callichthyidae), with comparisons with allied forms - Lam, Shu Him (2025)
Corydoradinae is the most species-rich group of the Neotropical catfish family Callichthyidae. However, the remarkably diverse and complex colour patterns characteristic of the group have been both a boon and bane to its taxonomy. Here, we investigated the taxonomic identity of Hoplisoma julii, a classic example of that issue. The species was described more than a century ago based primarily on colouration and very limited morphological data. To fully explore its species boundary and accurately delimit the species, we employed an integrative approach combining morphological data and COI divergence, based on samples from seven river drainages. Our results indicate that H. julii is a polymorphic species widely distributed in Rio Parnaíba and Eastern Amazonian drainages, but apparently similar morphotypes from Rio Curuá-Una actually represent a new species. A formal taxonomic description of this new spotted Hoplisoma species, commonly known in aquarium trade as CW037, is herein provided. These two species share very close genetic relationships in our Bayesian-inferred phylogeny, corroborating morphological data. Molecular delimitations also reveal the presence of a putative new species from Rio Purus, but its taxonomic identity is not assigned herein due to the paucity of morphological data. The delimitation results raise doubts about the identity of H. julii voucher specimens available in online genetic sequence repositories, highlighting the need for improved data curation.